2006
DOI: 10.1016/j.spmi.2006.06.015
|View full text |Cite
|
Sign up to set email alerts
|

Deep SiC etching with RIE

Abstract: SiC is currently an important topic in power devices. This new technology leads to lower power losses, faster switching, and higher working temperature. The design of SiC power devices requires the integration of edge termination techniques to obtain a high blocking voltage. The mesa structure approach is one wellestablished method. It could be used alone or in combination with a Junction Termination Extension (JTE). The mesa consists of a structure that removes material around the pn-junction. Due to the stro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 7 publications
0
29
1
Order By: Relevance
“…It was reported that this ratio was optimal to get the highest etch rate in SiC etching. 24 The surface roughness after 30 min etching is shown in Figure 1(a). Small spikes, oriented in the same direction, can be seen among indistinguishable roughness features.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that this ratio was optimal to get the highest etch rate in SiC etching. 24 The surface roughness after 30 min etching is shown in Figure 1(a). Small spikes, oriented in the same direction, can be seen among indistinguishable roughness features.…”
Section: Resultsmentioning
confidence: 99%
“…The result is consistent with the reference. 24 In the 5 Pa-work pressure series, the etching power is 200 W and the etching time is 480 min. Different form the 3.5 Pa-work pressure series, the spike density is very high as shown in Figure 4.…”
Section: Resultsmentioning
confidence: 99%
“…The maximum breakdown voltage it could achieve is almost the same as the parallel plane breakdown voltage when D1 is equal to and more than 6 μm. However, in reality the etching depth of the mesa JTE would not normally go beyond 5 μm, since this would degrade the surface roughness significantly as reported in literature [12] and it is a challenge in terms of processing to have a mask that could withstand the long time etch of SiC. Fig.4 shows the 2-D electric field distribution of twosteps JTE with different etching depth D1 and whilst keeping D2 and W constant, and Fig.5 shows their corresponding breakdown voltages.…”
Section: Design and Simulationmentioning
confidence: 98%
“…The more appropriate dry plasma etching, Reactive Ion Etching (RIE), may be used in separating the diode mesa. Patterning of mesas may be carried out with photoresists: AZ 5214 (standard) and TI 35 ES (special photoresist for deep RIE Si etching) (Lazar et al, 2006). A titanium/nickel (Ti/Ni) bilayer metal can be evaporated onto the sample.…”
Section: (Iii) the Oxide Layer From The P ++ -Side Can Then Be Removementioning
confidence: 99%